A Comparative Perspective on Fee Policies Used in OECD Countries for Financing Higher Education - Çetinkaya, Reşit; Çavdar, Ertuğrul (Bilgicagi Education Consulting and Publishing Industry Trade Limited Company, 2024)
One of the biggest problems faced by countries globally is the financing of higher education. Especially in the face of increasing demand for higher education and limited public resources, countries are in need of reform in terms of financing higher education. In recent years, there has been a global trend towards the adoption of higher education financing strategies that focus on cost sharing. The purpose of this study is to examine the higher education financing policies of countries with different systems compared to Turkey, to address the financial challenges in Turkish higher education financing, to recognize alternative financing options and to suggest strategies for Türkiye to expand its financing sources. For this reason, the study is “descriptive” and the data on the countries are analyzed by using the “documentary scanning” method. A comparative perspective on higher education financing is presented by analyzing the current higher education financing policies in OECD countries and their current remuneration schemes. The study covers all OECD member countries. As a sample, the current state of financing models and fee structures in seven countries, including the United States, Australia, Germany, the United Kingdom, China, Japan, Russia, the United States, Australia, Germany, the United Kingdom, China, Japan and Russia, each with different higher education finance policies, are presented. In order to improve higher education financing in Türkiye, it is suggested that the “Income- Contingent Loan” method, which is offered to the student on an optional basis in the collection of debts in higher education financing systems, should be implemented as an alternative student borrowing method, even if it is not generally used in every country.
Keywords: OECD; ICL; Higher education; financing; cost sharing; Other Fields of Education (Other); Alan Eğitimleri (Diğer); 4. Education; 1. No poverty